Evaluasi Kualitas Aplikasi Ruangguru Terhadap Kepuasan Pengguna Menggunakan Metode EUCS (End-User Computing Satisfaction) dan IPA (Importance Performance Analysis) - Muhammad Ainu Yazid; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Ruangguru is the largest and most comprehensive technology company in Indonesia focusing on education based services. The company was founded in 2014 by Belva Devara and Iman Usman. Later in 2016, Ruangguru launched a mobile application that useful for distance learning thus providing easy access for its users. The users of this application itself are students of Elementary, Junior High, and High School. However, in the application of technology and information especially in the product based mobile/smartphone application to the community, always have a diverse assessment of the application product. Therefore, the community always prioritizes quality content and the accuracy of the information presented. Therefore, the purpose of this research is to know the quality of Content, Accuracy, Format, Ease of Use, Timelines in the Ruangguru apps based on user experience with End-User Computing Satisfaction (EUCS) method. Data collection is obtained from the dissemination of questionnaires then conducted descriptive analysis and importance performance analysis (IPA) method which assesses the performance of Ruangguru apps based on the importance of each existing variable. The population characteristics in this study are users of Ruangguru itself focused on Elementary, Junior High, and High School students with sampling techniques using random sampling amounting to 100 respondents.